2015
DOI: 10.3141/2512-02
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Characteristics and Transport Policy Analysis in Large-Scale Residential Areas on a City Periphery

Abstract: Big cities in China are reforming their old downtown areas and demolishing substandard housing. The government relocates residents to large-scale residential areas on the city periphery, where the residents often find transport service unsatisfactory. However, in the search for policies that could be applied to ease this problem, there were no studies supplying effective quantitative forecasts that assessed improvements in travel quality in such areas. To provide a policy scenario forecast that could measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Travel modes other than cars can be considered as environmentally friendly modes, and the two primary modes can be divided into car travel (19.9%) and environmentally friendly travel (80.1%). Compared with the results of a 2011 diary survey [33], the rate of car use in our study reflects a significant increase. That change is reasonable, since our sample comes largely from the age group encompassing youth to middle age.…”
Section: Data and Preliminary Analysiscontrasting
confidence: 73%
“…Travel modes other than cars can be considered as environmentally friendly modes, and the two primary modes can be divided into car travel (19.9%) and environmentally friendly travel (80.1%). Compared with the results of a 2011 diary survey [33], the rate of car use in our study reflects a significant increase. That change is reasonable, since our sample comes largely from the age group encompassing youth to middle age.…”
Section: Data and Preliminary Analysiscontrasting
confidence: 73%
“…Cervero and Day studied the impacts of the relocation to outlying areas in Shanghai, finding that job accessibility levels declined dramatically following the move, matched by increased motorized travel and longer commute durations (Day & Cervero, 2010;Cervero & Day, 2008;Day, 2009). So, when studying the relocatees' travel characteristics and travel behaviors, researchers indicated that relocation policy decision making should consider relocatees' travel needs as a major factor, instead of what was done in this policy making process previously (Day & Cervero, 2010;Cervero & Day, 2008;Day, 2009;Pan, Wang, & Day, 2010;Guan & Zhang, 2011;Guan, 2012Guan, , 2013Guan & Yang, 2015). In addition, some studies did touch upon transit captivity issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is chosen as the case study city. In Shanghai, the megacity peripheral relocatees' area is called Large-Scale Residential Area on the City Periphery (Guan & Yang, 2015;Guan & Xu, 2018). In this research, "large-scale residential area" means an area of 2 km2 or more, with a population of 30,000 to 50,000, that has a major function of providing affordable housing and residence.…”
Section: Survey Sitementioning
confidence: 99%
“…In terms of supply, for central urban areas in the urban agglomeration, public transportation networks are usually well developed and connected, offering high accessibility for citizens. On the other hand, in the peripheral residential areas, the development of the public transportation system is usually lagging [3]. The poor transport connections at the home end, as well as the absence of efficient public transportation to potential destinations, can prevent people from transjurisdictional traveling and lead to social exclusion.…”
Section: Introductionmentioning
confidence: 99%